Penanaman Karakter Mandiri dan Kreatif Melalui Pembelajaran Tematik Bermuatan IPS pada Siswa Kelas V di SD N 1 Sekarsuli Banguntapan Bantul - Anisa Rahma Fauziah; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study is to know the implementation of independent and creative character planting through thematic learning of IPS-charged in grade V students of SD N 1 Sekarsuli Bantul. This research is qualitatively descriptive. The results showed that: (1) The implementation of self-character planting includes getting used to students tidying up classes, guiding students to always complete their own tasks, and guiding students to be confident. The cultivation of creative characters includes teachers being democratic and open, and freeing students to express opinions and ask questions. (2) Supporting factors include caring parents, encouragement from friends, teachers, and schools, active students. While the inhibition factors include the character of students who are hard to care about, the attitude of teachers who are not right, and the lack of support from parents. (3) The solution in overcoming the obstacles of character planting is that the principal holds regular meetings for all teachers, teachers cooperate with the parents of students, teachers approach their students, teachers give punishment in the form of additional tasks.